RANCANGAN PENGELOLAAN SISTEM INFORMASI SDM PADA PT. VICTORY TECHNOLOGI ABADI: SYSTEM, INFORMATION, HR, WATERFALL MODEL - Riswan; Rolisman (FORTECH (Journal of Information Technology), 2020)
Organizational management in the company is very important part to achieve organizational goals. Many factors must be considered in the management of organizational management related to human resources (HR). Rapid development and advancement of information and communication technology (ICT), external and internal environmental factors, international competition, uncertain global economic conditions. All this encourages companies to look for new ways to be able to utilize human resources more effectively. PT. Victory Techology Abadi utilizes ICT in the management of human resources that is still in the management of the management of a digital organization, by developing computer-based information systems. This system is designed with the waterfall diagram model approach with step 1. Requirement analysis, 2. Design, 3. Implementation, 4. Testing, 5. Maintenance. The results of the development carried out has resulted in a computer programmer application for HR management. This system is expected to be able to manage all organizational management activities of PT. Victory Technology better.